Faktor-Faktor Yang Mempengaruhi Niat Pembelian Produk Hankuspi: Studi UMKM Wirausaha Wanita di Bekasi - Yunita Ramadhani RDS; Edy Saptono (Fakultas Ekonomika dan Bisnis, Universitas Stikubank, 2020)
The use of environmentally friendly products as a solution to global warming continues to be improved in all aspects. The HANKUSPI (Coffee Wrap Handicraft) product is one of the products of MSMEs that is environmentally friendly, because it is only made from the remaining coffee packs. However, the demand for environmentally friendly products especially HANKUSPI is relatively low. This research will discuss about increasing purchase intention through product design, perceived behavioral control, subjective norms, and attitude as intervening variables. The sampling collection technique uses a purposive sampling method. 160 respondents will be used as respondents. The results of the study prove that there is a positive influence of subjective norms on the intention to purchase HANKUSPI products indirectly through the attitudes of green consumers. The perceived behavioral control does not affect the purchase intention of HANKUSPI products. However, product design has an influence on purchase intentions.